2016
DOI: 10.17221/233/2015-swr
|View full text |Cite
|
Sign up to set email alerts
|

Using magnetic susceptibility mapping for assessing soil degradation due to water erosion

Abstract: Jakšík O., Kodešová R., Kapička A., Klement A., Fér M., Nikodem A. (2016): Using magnetic susceptibility mapping for assessing soil degradation due to water erosion. Soil & Water Res., This study focused on developing a method for estimating topsoil organic carbon content from measured massspecific magnetic susceptibility in Chernozems heavily affected by water erosion. The study was performed on a 100 ha area, whereby 202 soil samples were taken. A set of soil samples was divided into 3 subsets: A (32 samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
(52 reference statements)
1
12
0
1
Order By: Relevance
“…Taking into account the fact that the present experimental data are coming from different soil profiles developed at different landscapes, climate, and parent material influences, the obtained correlation strongly warrants the applicability of magnetic susceptibility as a suitable “functional characteristic” for soil's SOC content (Vogel et al, ). Similar results on a local scale have been reported for natural Haplic Chernozems from south Moravia (Czech Republic) by Jakšık et al () and Calcisols from Spain (Quijano, Chaparro, Marié, Gaspar, & Navas, ). The negative trend, observed for the forest soils, developed on strongly magnetic parent material (granite; Figure b), reflects the dominance of the lithogenic magnetic fraction in the soil magnetic properties and the increasing concentration of strongly magnetic coarse magnetite grains with depth.…”
Section: Discussionsupporting
confidence: 88%
“…Taking into account the fact that the present experimental data are coming from different soil profiles developed at different landscapes, climate, and parent material influences, the obtained correlation strongly warrants the applicability of magnetic susceptibility as a suitable “functional characteristic” for soil's SOC content (Vogel et al, ). Similar results on a local scale have been reported for natural Haplic Chernozems from south Moravia (Czech Republic) by Jakšık et al () and Calcisols from Spain (Quijano, Chaparro, Marié, Gaspar, & Navas, ). The negative trend, observed for the forest soils, developed on strongly magnetic parent material (granite; Figure b), reflects the dominance of the lithogenic magnetic fraction in the soil magnetic properties and the increasing concentration of strongly magnetic coarse magnetite grains with depth.…”
Section: Discussionsupporting
confidence: 88%
“…The structure of the loess sample (L) is the most homogenous with isolated large capillary pores, which is typical for loess material (Kodešová et al, ). Jakšík et al (, ) and Zádorová, Jakšík, et al () also demonstrated that the stability of aggregates (expressed using the index of water stable aggregates proposed by Nimmo & Perkins, ) was highest in the chernozems (B1 and B2), followed by the regosol (B3) and the colluvial soils (B4 and B5). The larger stability of the aggregate may ensure the larger stability of pathways for a gas transport during the wetting and thus better conditions for microbial activity (optimal soil aeration) and pore connectivity for H 2 O and CO 2 transport and vice versa.…”
Section: Resultsmentioning
confidence: 97%
“…Because soil respiration highly depends on an organic carbon content in a soil ecosystem (Raich & Schlesinger, 1992), this process may differ considerably in different positions in the field based on the high organic carbon content spatial variability. Zádorová, Jakšík, Kodešová, & Penížek (2011); Zádorová, Penížek, Šefrna, Rohošková, & Borůvka (2011); Jakšík et al (2015); and Jakšík et al (2016) reported that the soil erosion and deposition of the soil material in geomorphologically diverse areas lead to changes of soil properties including organic carbon content. Alterations of the soil properties may result in soil respiration changes.…”
mentioning
confidence: 99%
“…Diverse soil conditions at different localities (e.g., topographic maps and selected terrain attributes, soil type descriptions and their distributions within the entire studied areas, distributions of soil properties as a Cox content, pH, soil texture, etc.) were also described by Jakšík et al (2015Jakšík et al ( , 2016, Penížek et al (2016), Sagova-Mareckova et al (2016), Vašát at et al (2014, 2015a, b, 2017a, and Zádorová et al (2011aZádorová et al ( , b, 2013Zádorová et al ( , 2014Zádorová et al ( , 2015. Soils within the Chernozem area (Brumovice) are the most explored followed by soils within the Luvisol area (Vidim) and both Cambisoils areas (Sedlčany and Železná).…”
Section: Study Areas Soil Sampling Field and Laboratory Measurementsmentioning
confidence: 96%